A Igreja e seu rosto histórico. Modelos de Igreja e modelo de Igreja na cidade - Cipolini, Pedro Carlos (Revista eclesiástica brasileira, 2001)
The Author asks: Being that the Church carries in its past historical experience the distinction of various faces, has not the moment arrived for it to seek out a new face? In effect, in the polycentric, conflictive and dynamic reality of present-day urban life, the pastoral work after results is outdated. The countenance of a new face of the Church – the Community of the Gospel of love-service – should be distinguished by mercy and welcoming fraternity.